HUBUNGAN ANTARA ACTIVITIES SPECIFIC BALANCE CONFIDENCE SCALE DENGAN UMUR DAN FALLS PADA LANSIA DI POLIKLINIK GERIATRI RSUP SANGLAH DENPASAR - Yuna Ariawan, IW; Kuswardhani, RA Tuty; Astika, IN; Suka Aryana, IGP (journal of internal medicine; Vol. 12, No. 1 Januari 2011, 2012)
Falls are a major health problem for elderly. Apart from the direct injuries resulting from falls, other long-term consequences may include disability, fear of falling, and loss of independence, which can have serious effects on people?s health and quality of life. These risk factors are categorized into two distinct groups: intrinsic and extrinsic factors. Psychological factors, more commonly referred to the ?fear of falling syndrome?, have been linked to signi! cant reductions of daily activities in fallers resulting in a loss of independence. The Activities-Speci! c Balance Con! dence (ABC) scale was used to measure con! dence in carrying out speci! c activities without falling or becoming unsteady. We conduct an analytic cross-sectional study to determine association between ABC scale with age and falls in elderly. Fifty two elderly outpatient, age over 60 years at Geriatric Clinic Sanglah Hospital Denpasar on January 2010 recruited for this study. All subjects were asked questionnaire of ABC scale and history of falls. Health status was taken from physical examination and medical records. Data were analyzed using SPSS software 17 version. There were 52 elderly outpatient consisted of 26 (50%) men, 26 (50%) women, age range 61 ? 87 years, mean 70.6 ± 6.5 years, and 17.3% of them have history of falls. Total ABC scale mean were signi! cantly difference between women and men (81.2 ± 14.1 vs 90 ± 12.8 p < 0.05); OA and without OA (80.5 ± 18.1 vs 88.6 ± 10.3 p < 0.05); and between faller and nonfaller (73.5 ± 13.6 vs 88.2 ± 12.9 p = 0.01). There was no signi! cant correlation between ABC scale and age. The ABC scale with cut off 82.9 has signi! cantly association with falls p = 0.01; prevalence ratio = 7.0 95%CI 1.6 ? 49.8; 74.4% sensitivity, 78% speci! city. As a conclusion we found lower total ABC scale has signi! cantly association with falls in elderly and has good sensitivity and speci! city on scale below 82.9%.
Keywords: ABC scale, falls, elderly